The Impact of CSR on Brand Identification, Word of Mouth and Consumer’s Repurchase Intention in the Retailer Industry - Thi Hong Nguyet Nguyen; Nguyen Khanh Hai Tran; Khoa Do; Van Dung Tran (Emerging Science Journal, 2023)
This study explored and measured the influence of corporation social responsibility (CSR) on consumers' re-purchase intentions through the mediators of brand identification and word of mouth (WOM). The quantitative method was applied in the research, and there were 287 valid respondents who had purchased something from the retailer store brands. The collected data was checked for reliability, convergence, and discriminant validity among the constructs before testing the hypothesis and the theoretical research model. In particular, the Cronbach alpha reliability, exploring factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation model (SEM) were used to analyze the research data under the support of SPSS and AMOS software. The results indicate that CSR has significant effects on brand identification, WOM, and consumers' re-purchase intentions. Brand identification has a positive impact on consumers' repurchase intentions, whereas WOM has not. The findings have significant contributions to the marketing theory and provide management implications for managers, especially in retail store brands. Doi: 10.28991/ESJ-2023-07-06-021 Full Text: PDF